Molecular Basis of the Structure and Transmission of SARS-CoV, SARS-CoV-2, and MERS: A Review Report: Review Report on SARS and MERS - Naz, Saima; Chatha, Ahmad Manan Mustafa; Durali DANABAS; Arshad, Aqsa (BioScientific Review, 2023)
In late 2019, a new coronaviridae family member officially designated as “Severe Acute Respiratory Syndrome Coronavirus-2” (SARS-CoV-2) emerged and began to spread intensely, worldwide. Its rapid spread was declared as a pandemic by the World Health Organization (WHO) in March 2020. Within the coronaviridae family, SARS-CoV-2 is the third highly pathogenic virus that infects human beings, following the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and the Middle East Respiratory Syndrome Coronavirus (MERS-CoV). In this review, the molecular basis for the origin, mode of action, invasion, and organization of these viruses are discussed by using various models. Moreover, the transmission pathways, replication mechanisms, and diagnostic strategies of these viruses are also discussed. The molecular basis of SARS and MERS helps to understand their infection patterns, pathogenic mechanisms with anecdotes on their diagnosis, and future directions. Expectedly, this study would serve the purpose of being a reliable source of information to scientists, clinicians, as well as the general public.